(x-8)(x-8)-81=0

Simple and best practice solution for (x-8)(x-8)-81=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-8)(x-8)-81=0 equation:


Simplifying
(x + -8)(x + -8) + -81 = 0

Reorder the terms:
(-8 + x)(x + -8) + -81 = 0

Reorder the terms:
(-8 + x)(-8 + x) + -81 = 0

Multiply (-8 + x) * (-8 + x)
(-8(-8 + x) + x(-8 + x)) + -81 = 0
((-8 * -8 + x * -8) + x(-8 + x)) + -81 = 0
((64 + -8x) + x(-8 + x)) + -81 = 0
(64 + -8x + (-8 * x + x * x)) + -81 = 0
(64 + -8x + (-8x + x2)) + -81 = 0

Combine like terms: -8x + -8x = -16x
(64 + -16x + x2) + -81 = 0

Reorder the terms:
64 + -81 + -16x + x2 = 0

Combine like terms: 64 + -81 = -17
-17 + -16x + x2 = 0

Solving
-17 + -16x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-1 + -1x)(17 + -1x) = 0

Subproblem 1

Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(17 + -1x)' equal to zero and attempt to solve: Simplifying 17 + -1x = 0 Solving 17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 0 + -17 -1x = 0 + -17 Combine like terms: 0 + -17 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17

Solution

x = {-1, 17}

See similar equations:

| y/5+y/4=7/5 | | -4(6y-5)-y=-3(y-2) | | 4k^2+12K-9=0 | | 1/5x+1/4=-2 | | 5/12X=3 | | 3/8X=24 | | 1/2X=11 | | 36r*5= | | -2y-7(6y-8)=1+9(1-y) | | E=LR+Lr | | 4/9X=20/18 | | r+6=3(r-3) | | x^3=29 | | 4/9X=10/18 | | 6r*5= | | 2r+6=3(3-r) | | 25v^2-64f^2=0 | | 5/7X=10/2 | | 6/12x=4/3 | | 10=-3x-17 | | 2/3x=5/6 | | 2s^2+15s+27=0 | | 5.07x=344.76 | | 3X+3(4-13)=96 | | 5/8x+9/15=7/5 | | x^2-113/9x+20/3=0 | | 5xy^2-2x^2y+x+5x^2= | | -5(6y-5)-y=-4(y-3) | | x(2x-18)-143= | | 5/3x+1/3x=3x+44/3+8/3x | | 2/x+2=5/4*x+17/8 | | 3x+17/12=8/3 |

Equations solver categories